Market Day as a Means of Financial Literacy Education for SDIT Siliwangi Students - Susanti, Illa; Pahala, Lamlam (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2023)
This research aims to activate the effectiveness of the 'Market Day' program as a means of financial literacy education for SDIT Siliwangi students. Using a qualitative descriptive approach, this research investigates how these activities influence students' understanding and attitudes towards financial management. Data was collected through direct observation of 'Market Day' activities, in-depth interviews with students, teachers and parents, as well as analysis of documents related to the program. Observations show student interactions in market simulations, focused on money management behavior, purchasing decisions, and savings practices. In-depth interviews provided insight into students', teachers', and parents' perceptions and experiences regarding the activities. Document analysis provides the context and educational goals of these activities. The results showed that 'Market Day' was effective in increasing students' understanding of the value of money, financial management and the importance of saving. Students develop calculation skills, make wise decisions in purchases, and realize the importance of saving for the future. In addition, this activity also supports the development of social skills and decision making. The 'Market Day' activity at SDIT Siliwangi offers a practical and interactive approach to financial literacy education, demonstrating the importance of integrating financial concepts in the elementary school curriculum. This research recommends using similar methods in other schools to increase financial literacy from an early age. This study also suggests further research to determine the long-term effects of financial literacy education on students' financial behavior